1998
DOI: 10.1164/ajrccm.157.1.9704125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Marrow Inflammatory Cell Progenitors after Inhaled Allergen in Asthmatic Subjects

Abstract: Increases in inflammatory cell progenitors, particularly eosinophil/basophil colony-forming cells (Eo/B-CFU), occur in peripheral blood after allergen provocation. The role of bone marrow (BM) in these reactions is unclear. We examined the effect of allergen challenge on human bone marrow progenitor cell growth. Fifteen asthmatic subjects, eight dual responders (DR) and seven isolated early responders (IER), were challenged with inhaled allergen. BM aspirates were taken before and 24 h after challenge and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
2
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 28 publications
3
92
2
8
Order By: Relevance
“…Furthermore, in humans this receptor also seems to be up-regulated by allergen exposure in asthmatics developing a late asthmatic reaction (15). This is in parallel with increased number of CFUs producing eosinophils in bone marrow samples taken after allergen exposure (24). Thus, allergen exposure seems to have slightly different regulatory effects in the bone marrow of allergic mice and asthmatic patients, although the models are similar in some respects because bone marrow activation can be observed in both species (24, 13-15, 20, 24).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in humans this receptor also seems to be up-regulated by allergen exposure in asthmatics developing a late asthmatic reaction (15). This is in parallel with increased number of CFUs producing eosinophils in bone marrow samples taken after allergen exposure (24). Thus, allergen exposure seems to have slightly different regulatory effects in the bone marrow of allergic mice and asthmatic patients, although the models are similar in some respects because bone marrow activation can be observed in both species (24, 13-15, 20, 24).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies in human and mouse systems have shown that local allergen exposure results in enhanced eosinophilopoiesis in BM. This prominently contributes to local eosinophilia, possibly via a feedback mechanism existing between the local tissue and BM, which triggers allergic inflammatory reaction [32][33][34]. Recent studies have shown that eosinophil precursors in BM are identifiable as CD34 + /IL-5R § + cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from changes in the bone marrow in asthmatic patients (Wood et al 1998), changes have also been found in the intestinal mucosa (Wallaert et al 1995). Studies on intestinal permeability by means of Cr-EDTA, demonstrated increased intestinal permeability by asthmatic patients as compared to healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%